(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2010)
An efficient mass propagation method for Feronia limonia was developed from excised shoot tips and nodal explants of in vitro grown seedlings. Explants were cultured on MS medium with different conc. of NAA, Kn, IAA and BAP singly or in combinations. Highest number of micro shoots and better plant growth were obtained from these two explants on MS medium supplemented with 0.2 mg/l BAP alone. The regenerated shoots were successfully rooted on MS medium supplemented with 0.5 mg/l NAA. The in vitro raised plantlets were successfully established in soil following the formation of roots with 100% survivability under ex vitro condition. Key words: Feronia limonia; Mass propagation; Node; Shoot tips; Multiple shoot DOI: 10.3329/bjsir.v45i1.5186 Bangladesh J. Sci. Ind. Res. 45(1), 75-78, 2010